Modelling S-Wave Velocity Structure Beneath the Central Main Ethiopian Rift Using Receiver Functions - Kibret, Birhanu A.; Ayele, Atalay; Keir, Derek (Frontiers in Earth Science, 2022)
We applied the receiver function (RF) technique on high-quality teleseismic earthquake data recorded by the RiftVolc broadband network from February 2016 to October 2017. We calculate RFs at 17 stations, which are inverted to estimate Vs, and Vp/Vs structure beneath the Central Main Ethiopian Rift and the Eastern plateau. The observed slow S-wave velocity (Vs) in the uppermost crust (<6 km depth) is interpreted as sedimentary and/or volcanic layers. Beneath the rift valley, crustal Vs is heterogeneous both laterally and with depth. In particular, slow Vs (∼2–3 km/s) is localised beneath volcanic centres in the upper-mid crust but ubiquitously slow in the lower crust with Vs as low as ∼3.5 km/s common. The slow lower crust is associated with high Vp/Vs ratios of ∼1.9–2.0. The Vs and Vp are consistent with the observed seismic velocities, and interpreted the presence of the small fraction (<5%) of partial melt from previous seismic imaging studies of the lower crust. In addition, the velocity contrast is small between the lower crust and upper mantle. The results suggest that partial melt in the lower crust beneath magmatically active rifts might be more widespread than previously thought and an important component of the magma plumbing system. In contrast, Vs is far more homogeneous and faster beneath the Eastern Plateau, with a distinct velocity contrast between the crust and upper mantle suggesting less crustal deformation than what is observed beneath the central rift zone.